The prepared leader - James, Erika H.; Wooten, Lynn Perry (Ascent Audio, 2022)
In no other time in recent history have leaders in every industry and on every continent grappled with so many changes that have independently and simultaneously undermined their ability to lead. The Prepared Leader encapsulates more than two decades of the authors' research to convey how it has positioned them to navigate through the distinct challenges of today and tomorrow. Their insights have implications for every leader in every industry and every worker at every level. In their must-listen, actionable book, James and Wooten provide tools and frameworks for addressing and learning from crises, and they provide insight into what you need to know to become a Prepared Leader, including: the five phases of crisis management and the skills you need for each phase; making the right decisions under pressure and how to avoid common mistakes; and building a crisis leadership team and how to lead one that you've inherited. James and Wooten argue that-in addition to people, profit, and the planet-prepared leadership should be the fourth "P" in a company's bottom line. They bring decades of world-renowned research on crisis leadership, diversity and inclusion, management strategy, and positive leadership to the table to help leaders better prepare themselves to lead through crises-and for whatever lies around the corner.